Cardiac rehabilitation in a patient with ankylosing spondylitis: A single-program, double-effect - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2019)
Ankylosing spondylitis (AS) is a chronic inflammatory disease which is characterized by the primary involvement of axial spine and sacroiliac joints and also extraarticular involvements including ophthalmological, cardiac, pulmonary, or neurological effects. Cardiac involvement in patients with AS has been reported to be 2 to 10%. Ventricular dysfunctions have been previously reported in patients with AS. However, there is only one case report describing primary cardiomyopathy due to AS and management with better control of inflammation and medications. Herein, we present a case of cardiomyopathy in AS in whom ejection fraction and New York Heart Association (NYHA) functional class improved and disease activity decreased after cardiac rehabilitation program
Keywords: Ankylosing spondylitis; cardiac rehabilitation; cardiomyopathy; HEART-FAILURE; ECHOCARDIOGRAPHIC EVIDENCE; DYSFUNCTION